On the maximum likelihood estimator for irregularly observed time series data from COGARCH models - Kim, Moosup; Lee, Sangyeol (Revstat, 2013)
* In this paper, we study the asymptotic properties of the maximum likelihood estimator (MLE) in COGARCH(1,1) models driven by Levy processes as proposed by Maller et al. ([13]). We show that the MLE is consistent and asymptotically normal under some conditions relevant to the moments of the driving Levy process and the sampling scheme. Key-Words: * COGARCH(1,1) models; maximum likelihood estimation; consistency; asymptotic normality; sampling scheme; irregular time spaces. AMS Subject Classification: * 62F12, 62M86.